A Case Study for Introducing African Cheetah in Kuno National Park Sheopur, Madhya Pradesh, India - (:unkn) unknown (My University, 2023)
Ecology, as a scientific discipline, operates on a well-established framework of principles that govern the functioning of ecosystems. In this research paper, we explore the tragic extinction of the Indian Cheetah (Acinonyx jubatus venaticus) and investigate the role of habitat alteration in its demise. The last known Indian Cheetah was fatally shot in 1952, within a habitat characterized by open grasslands and shrubs within the arid and sub-arid ecosystem. Subsequently, changes in the habitat forced the last surviving Cheetah to seek refuge in the wooded Sal (Shorea robusta) forest, situated in the then region of Madhya Pradesh. Introducing Cheetahs (Acinonyx jubatus) from South Africa and Namibia is the world’s first inter-continental large wild carnivore translocation project. This research paper critically examines the decision to introduce Cheetahs (Acinonyx jubatus) from Namibia as a conservation measure. While acknowledging the worsening ecological situation, this paper argues that such an action may have been taken hastily, without due consideration of the cheetah's guild ecology. 5 females, 3 males from Namibia, and 7 males, 5 females from South Africa were relocated to Kuno National Park on 17th September 2022 and 18th February 2023 respectively. The idea to introduce the African cheetah was first discussed in 2009. In 2013, a decision of the Forest Bench of the Supreme Court on Asiatic lion translocation found massive flaws with the proposed introduction of African cheetahs to Kuno. In an ambitious endeavor during 2022, African Cheetahs were carefully selected and introduced on an experimental basis into a specifically chosen habitat in India. Relocation of cheetah populations is considered by India to have vital and far-reaching conservation consequences, and to achieve a number of ecological objectives i.e., improving the enhancing the livelihood options and economies of the local communities and re-establishing the function role of chee
Keywords: African Research